THE NEED TO INCREASE THE INDEPENDENCE OF LOCAL BUDGETS IN UZBEKISTAN (American Journal of Business Management, Economics and Banking, 2023)
This article highlights ways to strengthen the revenue base of local budgets while ensuring their independence, the distribution of budget revenues, including taxes, between the republican and local budgets while ensuring their independence, the distribution of budget revenues, including taxes, between the republican and local budgets while ensuring the sustainability of local budgets.